Acute rotavirus diarrhea in pediatric patients - Bednarek, Jadwiga Janina (Journal of Education, Health and Sport, 2018)
Rotavirus is the most common cause of gastroenteritis. He is responsible for non-hospital and hospital gastrointestinal infections. It is a major epidemiological threat especially in the pediatric population. Acute diarrhea and dehydration cause 2 million hospitalizations and cause deaths of around 440,000 children annually. Rotavirus is also one of the most common aetiological factors of nosocomial infections in pediatric wards. The incidence of hospital RV infections ranges from 2.5 to 7.9 per 1000 days of hospitalization. It extends the stay from 1.7 to 7 days depending on the country [1,2,3,4]. Between 13 and 80% of children with RV infection require infusion therapy [1,2,5]. One of the most effective ways to reduce the incidence of RV infection is to immunize the body. There is evidence of the effectiveness of vaccination programs in both industrialized and developing countries [6]